Rancang Bangun Sistem Monitoring Dan Kontrol Penerbangan Jalan Komplek Perumahan Poltekbang Medan Berbasis Internet of Things - Jordan Simanjuntak, Mikhael; Liber Tommy Hutabarat; Muhammad Iqbal (CV. Hawari, 2025)
Street lighting plays a vital role in ensuring safety and comfort for road users at night. However, the lighting system in Poltekbang Medan Housing Complex is still operated manually without remote monitoring, leading to potential energy waste and inefficiency. This study aims to design an Internet of Things (IoT)-based street lighting monitoring and control system that enables real-time supervision via smartphone. The research method includes literature review, hardware and software design, and system testing. The main components are the ESP32 microcontroller, PZEM-004T sensor for electrical parameter measurement, and relay module for lamp control, integrated with the Blynk application through Wi-Fi connection. Test results show that the system can accurately display electrical data and respond well to control commands, with measurement deviations remaining within acceptable tolerance. The measured lighting intensity of 84 lux closely matches the calculated value of 85.2 lux and complies with the Indonesian National Standard (SNI) for secondary local roads. Therefore, the system is considered feasible as it enhances energy efficiency, accelerates fault handling, and improves safety and comfort through real-time remote monitoring and control.